SAMBUNGAN ANTAR PROVENANS DAN FAMILI Eucalyptus occidentalis UNTUK MENUNJANG PEMULIAANNYA DAN PENGARUH KARAKTER ENTRIS PADA PERTUMBUHAN TUNAS BARU - Rina Laksmi Hendrati (Jurnal Pemuliaan Tanaman Hutan, 2012)
In tree improvement program, vegetative propagules, including grafting, from improved materials will develop into individuals with the same genetic structures from its improved clonal sources. Vegetative propagules are also advantagous due to their earlier flowering and fruiting if compared to seedlings. Grafting success will be etermined by compatibilities between 2 different tissues from different genetic sources. In this study, grafting success of E. occidentalis between rootstocks and entries of different provenans and families were examined using scions collected from mature (6.5 year) trees to hasten deployment of improved genotypes. Reciprocal grafting between provenances with different provenance  rootstocks and scions were conducted with successvaried from none to complete survival. Abilities of two best provenans under waterlogging, Dumbleyung and Young River, to perform highest survival in grafting provide advantages for deployment of their genetic materials. Genotype differences between scions were more obvious to influence survival than between rootstocks. Small number of grafted plants initiated flowers 4 months after grafting. Scion diameter, length and initial leaves affect the growth of new shoots. The best E. occidentalis grafting success were determined by scion length of 2.5 - 4 cm, diameter of 6 - 7 mm with all leaves removed.